2015
DOI: 10.1038/srep13069
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year helium anomaly prior to the 2014 Mt Ontake eruption

Abstract: Mt Ontake in central Japan suddenly erupted on 27th September 2014, killing 57 people with 6 still missing. It was a hydro-volcanic eruption and new magmatic material was not detected. There were no precursor signals such as seismicity and edifice inflation. It is difficult to predict hydro-volcanic eruptions because they are local phenomena that only affect a limited area surrounding the explosive vent. Here we report a long-term helium anomaly measured in hot springs close to the central cone. Helium-3 is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
86
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 22 publications
3
86
0
Order By: Relevance
“…Input of magmatic fluid into Mt. Ontake's volcanic system had also been suggested by He isotopic ratios of summit fumaroles and flank hot springs (Sano et al 1984(Sano et al , 1986 He ratio at hot springs at about 4 km from the summit had been reported and is concluded as precursory increased input of magmatic fluid from the depth (Sano et al 2015). Supporting evidences for the input of magmatic fluids are also found in seismological studies.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Input of magmatic fluid into Mt. Ontake's volcanic system had also been suggested by He isotopic ratios of summit fumaroles and flank hot springs (Sano et al 1984(Sano et al , 1986 He ratio at hot springs at about 4 km from the summit had been reported and is concluded as precursory increased input of magmatic fluid from the depth (Sano et al 2015). Supporting evidences for the input of magmatic fluids are also found in seismological studies.…”
Section: Discussionsupporting
confidence: 54%
“…Ontake, the volume of the system needed may be drastically decreased. In fact, sustained magmatic fluid supply to the hydrothermal system has been indicated by helium-3 studies (Sano et al 2015). Sulfur brought by the long-term magmatic fluid supply might be a candidate for such accumulated sulfur in the hydrothermal system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the event was purely hydrothermal in that no juvenile material was erupted, there is considerable geochemical evidence that magmatic input was involved in the triggering of hydrothermal fluid migration. Gas samples over 10 years indicated a progression of He isotopes toward increasingly magmatic values prior to the 2014 event (Sano et al, 2015). Immediately after the eruption, SO 2 emission rates of >2,000 t/d were measured, and rapidly decreased thereafter, though hydrothermal H 2 S emissions continued (Mori et al, 2016).…”
Section: Speculations On the Connection Between Phreatomagmatic Activmentioning
confidence: 99%
“…Immediately after the eruption, SO 2 emission rates of >2,000 t/d were measured, and rapidly decreased thereafter, though hydrothermal H 2 S emissions continued (Mori et al, 2016). It appears likely that the eruption was at least partially triggered by input of magmatic gas at the base of the acidaltered hydrothermal system (Sano et al, 2015;Mori et al, 2016;Yamaoka et al, 2016).…”
Section: Speculations On the Connection Between Phreatomagmatic Activmentioning
confidence: 99%